Undressing masculinity: An exploratory study on men's embodied engagement with underwear. Issue 2 (1st August 2022) - Clancy, Johnathan; Barry, Ben
This article shares findings from an exploratory study on the relationship between men's embodied engagement with underwear and their practices of masculinity. Drawing on wardrobe interviews with nine men and object analyses of their underwear, we investigate how men understand the role of underwear in their lives, how they shift their underwear choices in different social contexts and how they experience their bodies through underwear. Our participants developed emotional bonds with their underwear, but their engagements with these items were restricted by gendered social pressures and boundaries. We argue that men use underwear as 'manhood acts' to provide themselves with comfort and confidence to navigate everyday life and, ultimately, shore up and affirm hegemonic masculinity. This article contributes to men's fashion scholarship on underwear by introducing the context of everyday dress practices to the existing focus on branding and advertising images. We encourage researchers to build upon our study on men's underwear by engaging participants whose demographics expand beyond our sample of primarily heterosexual, cisgender men who were under 35 years of age.